Numerical study of a vertical pullout capacity of strip anchor plate on a frictional soil - Hicham Mokhbi; Mekki Mellas; Abdelhak Mabrouki; Jean‐Michel Pereira (Journal of Applied Engineering Science and Technology, 2016)
This paper presents a numerical study of the ultimate pullout capacity of an isolated stripplate anchor, using the finite element method by Plaxis 2D software. The plate anchor is assumedrigid horizontally installed in a frictional soil and subjected to a centered vertical load. The soilbehavior is governed by an elastic‐perfectly plastic law, and Mohr‐Coulomb criterion was adopted.The ultimate pullout capacity is expressed in terms of pullout factor Nγ for different values of thedepth H and the internal friction angle of soil φ'. The numerical results obtained allow us topropose a simple relationship to calculate the pullout factor of a strip plate anchor embeddedhorizontally in frictional soil. The numerical results of this study are finally compared to thoseavailable in the literature.